2021
DOI: 10.21704/rea.v20i2.1809
|View full text |Cite
|
Sign up to set email alerts
|

CALIDAD MORFOLÓGICA Y BIOLÓGICA DE Pinus radiata D. Don, MICORRIZADO CON Scleroderma verrucosum (Vaill) Pers. Y Rhizopogon luteolus Fr. & Nordh. EN CONDICIONES DE VIVERO

Abstract: Se evaluó el efecto de Scleroderma verrucosum (Vaill) Pers y Rhizopogon luteolus Fr. & Nordh. sobre la calidad morfológica y biológica de plantas de Pinus radiata D. Don en vivero en Vilcashuamán, Ayacucho, Perú. Tratamientos: (1) Micorrización con Scleroderma verrucosum, (2) Micorrización con Rhizopogon luteolus, (3) Mezcla de ambos hongos y (4) Control, en un diseño completamente al azar con 10 repeticiones por tratamiento. Los hongos provinieron de bosques de Pinus radiata y Eucalyptus globulus de la lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Various regions of the Peruvian highlands are suitable for afforestation; however, in the definitive field, pine plants have a mortality rate that exceeds 50% [5]; mainly due to the fact that seedlings from nurseries or greenhouses do not have adequate quality for their survival [6]. The adequate humidity affects the different plantations from the germination of the seeds, as is the case of the pine species, which is evidenced in the study carried out by Sevik et al [7] where they found that most pine species are susceptible to water stress below -6 bar, reducing their germination to 30% of the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Various regions of the Peruvian highlands are suitable for afforestation; however, in the definitive field, pine plants have a mortality rate that exceeds 50% [5]; mainly due to the fact that seedlings from nurseries or greenhouses do not have adequate quality for their survival [6]. The adequate humidity affects the different plantations from the germination of the seeds, as is the case of the pine species, which is evidenced in the study carried out by Sevik et al [7] where they found that most pine species are susceptible to water stress below -6 bar, reducing their germination to 30% of the control group.…”
Section: Introductionmentioning
confidence: 99%